2016
DOI: 10.1136/acupmed-2015-011014
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture for Reproductive Hormone Levels in Patients with Diminished Ovarian Reserve: A Prospective Observational Study

Abstract: BackgroundEffective methods for the treatment of reproductive dysfunction are limited. Previous studies have reported that acupuncture can modulate female hormone levels, improve menstrual disorders, alleviate depression and improve pregnancy rates. However, studies of acupuncture for diminished ovarian reserve (DOR) are lacking.ObjectiveTo carry out a prospective observational study aimed at assessing the effect of EA on the reproductive hormone levels of patients with DOR seeking fertility support and consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…For example, acupuncture can reduce the burden of menopause-related symptoms, 37 increase levels of oestradiol, 38 treat premature ovarian failure 39 and improve diminished ovarian reserve. 40 These effects may be related to upregulation of gene and protein expression of components of the PI3K/Akt/ mTOR signalling pathway. 41 Our study suggests that acupuncture can improve ovarian hormone and oestrous cycle disorders, which is encouraging with respect to the potential role of acupuncture in the treatment of ovarian failure.…”
Section: Ea Simultaneously Improved Ovarian Cycle and Glucose Metabolismmentioning
confidence: 99%
“…For example, acupuncture can reduce the burden of menopause-related symptoms, 37 increase levels of oestradiol, 38 treat premature ovarian failure 39 and improve diminished ovarian reserve. 40 These effects may be related to upregulation of gene and protein expression of components of the PI3K/Akt/ mTOR signalling pathway. 41 Our study suggests that acupuncture can improve ovarian hormone and oestrous cycle disorders, which is encouraging with respect to the potential role of acupuncture in the treatment of ovarian failure.…”
Section: Ea Simultaneously Improved Ovarian Cycle and Glucose Metabolismmentioning
confidence: 99%
“…Wang et al and Zhou et al investigated effect of acupuncture on E2 level in human with diminished ovarian reserve and primary ovarian insufficiency, respectively [20, 22]. E2 level was increased in compliance with acupuncture treatment in the both studies.…”
Section: Resultsmentioning
confidence: 99%
“…Although there are few studies on the effects of acupuncture on children's sexual development and secondary sexual signs, there are relevant clinical and basic researches on the effects of acupuncture on adult women's reproductive endocrine function [19,20]; literature studies have shown that acupuncture treatment can reduce the serum FSH and LH levels of adult women, improve the E2 level of women, and improve menstrual cycle and ovarian function [21,22]; acupuncture has been applied to primary ovarian dysfunction [23], polycystic ovarian syndrome [24], [25], dysmenorrhea [26], and other female reproductive endocrine-related diseases. Although the mechanism of acupuncture on female reproductive endocrine system is not very clear at present, it has been found that acupuncture can regulate some neurotransmitters and neuropeptides, such as β-endorphin, dopamine, and prostaglandin [27][28][29] and then affect the hypothalamic pituitary gonadal axis, thus regulating the level of serum sex hormones [30].…”
Section: Discussionmentioning
confidence: 99%